AIM2-inflammasome role in systemic lupus erythematous and rheumatoid arthritis. (30th September 2022) - Uresti-Rivera, E. E.; García-Hernández, M. H.
Abstract: The inflammasome AIM2 regulates multiple aspects of innate immune functions and serves as a critical mediator of inflammatory responses. AIM2 inflammasome activation leads to the production of pro-inflammatory cytokines, IL-1β and IL-18 and participates triggering a pyroptosis response needed to counteract excessive cell proliferation. In addition, AIM2 expression and activation is wide regulated since alteration in its activity may derived in pathological consequences. Consequently, deregulated AIM2 activation contributes to the pathogenic processes of various inflammatory diseases. In this review, we will discuss the activation and function of AIM2 inflammasome, as well as its contribution in rheumatoid arthritis and systemic lupus erythematous pathology. Finally, we highlight the participation of the AIM2-inflammasome at the level of joint in rheumatoid arthritis and at kidney in systemic lupus erythematous. The development of therapeutic strategies based on modulation of AIM2-inflammasome activity should have a tissue-specific focus.